An extended model of theory of planned behaviour: Entrepreneurial intention, regional institutional infrastructure and perceived gender discrimination in India. Issue 3 (9th April 2019) - Kumar, Sushil; Das, Satyasiba
Abstract : Purpose: The purpose of this study is to provide an extended model of the theory of planned behaviour (TPB) and examine how institutional infrastructure and two social factors – peer effect and gender discrimination – determine entrepreneurial intention in emerging economies such as India. Design/methodology/approach: Using a structural equation modelling (SEM) approach, the proposed model is tested on a sample of 265 post-graduate students from the Indian Institute of Management campuses in India. Perceived gender discrimination is used as a grouping variable to test its impact in the model. Findings: The study found that peer effect has positive association with an individual attitude towards entrepreneurship. It also found positive moderating effect of institutional infrastructure on entrepreneurial intention in a regional entrepreneurial ecosystem, but in case of entrepreneurial self-efficacy, the result is non-conclusive. Further, our results establish that gender discrimination has varying influence but remains a significant factor to choose entrepreneurial career in emerging countries such as India. Research limitations/implications: The study adds to the understanding of drivers or antecedents to entrepreneurial intention, especially in emerging economy context and finds its usefulness in country such as India. It contributes to the existing model by empirically proving the role of peer effect and institutional infrastructure in emerging economies which are characterised by weak institutions and inadequate access to resources to start and sustain any entrepreneurial activity. Practical implications: The results make several implications for academic institutions, entrepreneurial ecosystem stakeholders and policy makers in emerging economies. The academic institutions, universities and incubation hubs can consider promoting a peer-group culture that strengthens individual's EI in emerging economies. Policy makers and stakeholders should build an encouraging entrepreneurial ecosystem with adequate institutional infrastructure to promote entrepreneurship. Originality/value: The authors extend research on entrepreneurial intention beyond individual factors (personal-level variables) and examine the contingent role of institutional infrastructure and socio-cultural factors (peer effect and gender discrimination). Whilst TPB successfully predicted entrepreneurial intention in Western settings, this study provides strong empirical evidence to this research in emerging countries.